Biodegradable behaviour of polylactic acid nanocomposite based on modified nanoclay - Norayuni, Azizi (2012)
Polylactic acid (PLA) is a unique polymer. Eventually, this polymer has the broadest range of application especially in biomedical field due to its biocompatibility characteristics. The main purpose of this research is to study on the biodegradable properties of PLA based on modified organoclay. The properties of PLA nanocomposite will be improved by adding nanoclay or Montmorillonite (MMT) and produce PLA nanocomposite. The MMT that used in this research is bis-(2-hydroxyethyl) methyl tallow alkyl ammonium cations (Cloisite B30). A series of PLA nanocomposite was classified by different percentage of compositions and the samples were analysed and compared with pristine PLA. PLA nanocomposite was produced by melt intercalation method using twin screw extruder. Then, the compounds were injection molded by injection molding method and formed dumbbell shape. Meanwhile, PLA nanocomposite is characterized by Scanning Electron Microscopy (SEM) and X–Ray Diffraction Analysis (XRD). However, SEM captures could not determine the dispersion of Cloisite B30 precisely nevertheless it illustrates that aggregates were formed in the images. XRD result supported an exfoliation nanocomposite was possible demonstrated as no diffraction peak was appeared in the XRD results. It also shows that the inter-galleries spacing of the Cloisite B30 between PLA matrixes is too wide. Subsequently, the samples were tested using accelerated weathering tester for biodegradable analysis. Finally, the samples before and after exposed in the accelerated weathering tester were examined by mechanical testing to determine mechanical properties such as ultimate strain, elastic modulus and ultimate stress using tensile strength testing. The most desired result of this research is based on the biodegradable testing. After a year observation, only pristine PLA was sustained in strength while the PLA nanocomposite is so brittle. Meanwhile for a year and half observation, all the samples were so brittle. It can be concluded that the pristine PLA is still remain sustain after a year but it start to degrade after a year and half. The result obtained for before exposing under accelerated weathering tester, the pristine PLA possesses good properties for ultimate strain and ultimate stress rather than elasticity behaviour.